Moving on [videorecording (DVD)] - Weitz, Paul, 1966-; Fonda, Jane, 1937-; Tomlin, Lily; McDowell, Malcolm, 1943-; Burns, Sarah (Actress); Roundtree, Richard, 1942- (Lionsgate, 2023)
Claire and Evelyn are estranged friends who reunite to get even with Howard, the petulant widower of their recently deceased best friend. Along the way, Claire reunites with Ralph, her great love from her younger years, as each woman must make peace with her past and learn to treasure the value of a good friend.